Corpus Stylistics in Heart of Darkness and its Italian Translations. - Mastropierro, Lorenzo (Corpus and Discourse, 2017)
"This book explores the interaction between corpus stylistics and translation studies. It shows how corpus methods can be used to compare the style of literary texts to that of their translations, through the study of Joseph Conrad's Heart of Darkness and four of its Italian versions. The comparison focuses on textual patterns and investigates their role as building blocks of fictional worlds. By combining quantitative and qualitative analysis, the book demonstrates that alterations to the original's linguistic features affect the representation of the fictional world in translation. This illuminates the manipulative effects that translating can have on the reception of a text, as changes in the fictional world may trigger different readings. The analysis illustrates how corpus methods can unveil the impact of translation on the connection between the formal and the interpretational level in literary texts. This book relates corpus linguistics, stylistics, and translation studies, contributing to the multidisciplinary application of corpus approaches to the study of literary translation and is a useful read for researchers and students of both corpus stylistics and translation studies."--